Branding Strategies Affecting Foreign Tourists’ Decision To Participate The International Marathon Events - Krongyut, Khwanruethai; Choibamroong, Therdchai (International Journal of Psychosocial Rehabilitation, 2020)
Marathon has become a phenomenon that is popular with more than 30 million people worldwide each year. For this reason, the marathon has become a popular sport activity that has grown rapidly over the past decade. The International Marathon in Thailand is steadily gaining increased interest from runners both in domestic and overseas and generates revenue from the enormous number of runners participating in the competition each year. However, the image of Thailand international marathon is not as clear as the global marathon, such as Boston Marathon, London Marathon, and Tokyo Marathon. This research therefore emphasizes on the analysis of branding strategies that can attract runners from all over the world to participate in the international marathon in Thailand and create a memorable image of Thailand as an international marathon destination. The study followed quantitative approaches, collected data from 400 runners who had attended to the international marathons event in Thailand, and analyzed by descriptive statistic and multiple linear regression analysis.